Analisis Perubahan Struktur Ruang Rencana Teknis Satuan Pemukiman (RTSP) Transmigrasi UPT. Tongauna, Kabupaten Kolaka Timur - Hasbullah Syaf (Universitas Halu Oleo, 2022)
ABSTRACT The transmigration paradigm changed from central to regional government policies. Meanwhile, the current condition of land for proper transmigration is very difficult to obtain, so it is shifting towards forest areas. The purpose of this study is to analyze changes in the structure of the RTSP space so that the condition of protected forests and buffer areas is well maintained and sustainable. This study used the current RTPS location comparison survey method and the results of future RTSP analysis. The results obtained (a) the measured area of UPT Tongauna is 1,040.49 and the area that can be used for transmigration settlement land covering an area of 200 ha which can accommodate as many as 100 households with the TPLK pattern; (2) to maintain forest sustainability, there is a change in the Border or Buffer Zone of the RTSP location and forest area from 100 Ha to 553 Ha; and (3) the transfer of the LU II location which was originally located in the Production Forest Area (HP) after an analysis, the transfer of the kapling/parcel to the new spatial location was carried out. In an effort to avoid environmental damage, land clearing should use more manual systems to avoid excessive land and forest use.Keywords: RTSP, Transmigration, UPT. Tongauna, Spatial Structure.ABSTRAK Paradigma transmigrasi berubah dari kebijakan pemerintah pusat ke daerah. Sementara kondisi lahan untuk transmigrasi yang layak saat ini sangat sulit diperoleh, sehingga bergeser ke arah kawasan hutan. Tujuan penelitian ini adalah untuk menganalisis perubahan struktur ruang RTSP agar kondisi hutan lindung dan kawasan penyangga terjaga dengan baik dan berkelanjutan. Penelitian ini menggunakan metode survei perbandingan lokasi RTPS saat ini dan hasil analisis RTSP ke depan. Hasil yang diperoleh (a) luas terukur UPT. Tongauna adalah 1.040,49 dan Luasan areal yang dapat dimanfaatkan untuk lahan permukiman transmigrasi seluas 200 Ha yang dapat menampung sebanyak 100 KK dengan pola TPLK; (2) untuk menjaga kelestaria hutan maka terjadi perubahan Sempadan atau Buffer Zone lokasi RTSP dan Kawasan hutan dari 100 Ha menjadi 553 Ha; dan (3) pemindahan lokasi LU II yang semula terletak dalam Kawasan Hutan Produksi (HP) setelah dilakukan analisis maka dilakukan pemindahan kapling/persil pada lokasi tata ruang yang baru. dalam upaya untuk menghindari kerusakan lingkungan maka pembukaan lahan sebaiknya lebih banyak menggunakan sistim manual untuk menghindari pemanfaatan lahan dan hutan yang berlebihan.Kata Kunci: RTSP, Transmigrasi, UPT. Tongauna, Struktur Ruang